Gram‐Scale Aqueous Synthesis of Stable Few‐Layered 1T‐MoS2: Applications for Visible‐Light‐Driven Photocatalytic Hydrogen Evolution. Issue 41 (31st August 2015) - Liu, Qin; Li, Xiuling; He, Qun; Khalil, Adnan; Liu, Daobin; Xiang, Ting; Wu, Xiaojun; Song, Li
Abstract : Most recently, much attention has been devoted to 1T phase MoS2 because of its distinctive phase‐engineering nature and promising applications in catalysts, electronics, and energy storage devices. While alkali metal intercalation and exfoliation methods have been well developed to realize unstable 1T‐MoS2, but the aqueous synthesis for producing stable metallic phase remains big challenging. Herein, a new synthetic protocol is developed to mass‐produce colloidal metallic 1T‐MoS2 layers highly stabilized by intercalated ammonium ions (abbreviated as N‐MoS2 ). In combination with density functional calculations, the X‐ray diffraction pattern and Raman spectra elucidate the excellent stability of metallic phase. As clearly depicted by high‐angle annular dark‐field imaging in an aberration‐corrected scanning transmission electron microscope and extended X‐ray absorption fine structure, the N‐MoS2 exhibits a distorted octahedral structure with a 2 a 0 ×  a 0 basal plane superlattice and 2.72 Å Mo–Mo bond length. In a proof‐of‐concept demonstration for the obtained material's applications, highly efficient photocatalytic activity is achieved by simply hybridizing metallic N‐MoS2 with semiconducting CdS nanorods due to the synergistic effect. As a direct outcome, this CdS:N‐MoS2 hybrid shows giant enhancement of hydrogen evolution rate, which is almost 21‐fold higher than pure CdS and threefold higher than corresponding annealed CdS:2H‐MoS2 . Abstract : Gram‐scale aqueous synthesis of 1T‐MoS2, highly stabilized by intercalated ammonium ions, is demonstrated. In combination with X‐ray absorption spectra and atomic structure observations, the correlation between microstructure and stable metallic phase is revealed, agreeing with density functional calculations. More interestingly, highly efficient hydrogen evolution is achieved by hybridizing the 1T‐MoS2 with semiconducting CdS nanorods.